The Effectiveness of Life Therapy on Psychological Well-Being and Hope in Patients with Irritable Bowel Syndrome - Fatemeh Bahari; Ramezan Hassanzadeh; Mohammadkazem Fakhri (روانشناسی و روانپزشکی شناخت)
Introduction: One of the most common chronic gastrointestinal diseases is irritable bowel syndrome, which can influence patients’ cognitive, emotional, and psychological processes. Objective: The present research aimed to determine the effectiveness of life therapy on psychological well-being and hope in patients with irritable bowel syndrome. Method: This research was a semi-experimental pretest-posttest design with a control group. The study population consisted of all patients referring to private gastroenterology clinics in the city of Sari in 2021 with complaints of irritable bowel syndrome symptoms. A total of 30 patients were selected through a purposive sampling method and were randomly assigned to two groups: Experimental (n=15) and control (n=15). The Psychological Well-Being Scale (Ryff et al., 1980), the Hope Scale (1999), and the Life Therapy Protocol (Hassanzadeh, 2020) were used for eight 90-minute sessions to collect data. Multivariate analysis of covariance (MANCOVA) using SPSS version 22 was employed to analyze the data. Results: The results of the covariance analysis demonstrated a significant difference between the scores of the control and experimental groups (P = 0.001). Overall, life therapy led to an increase in the total scores of psychological well-being and hope among patients with irritable bowel syndrome. Conclusion: Results revealed that psychotherapy culminated in increased psychological well-being and hope in patients with irritable bowel syndrome. Therefore, life therapy can be utilized as an adjunctive, supportive, and rehabilitative intervention alongside drug therapy to improve rehabilitation outcomes and enhance the quality of life for patients.